(untitled) (Per Musi, 2011)
The text approaches the meanings of ‘wonder’ in the context of the Afro-Brazilian ritual called the ‘Reign of Our Lady of the Rosary’, according to the way it is applied in the songs’ lyrics and in participants’ verbal discourses. Analyses were based on participants’ perspectives about the origin and history of their religious tradition, which is based on their enslaved ancestors’ experiences of pain. Those facts and events still highlight the sense of belonging to this tradition nowadays and make their performative acts meaningful, significant and thus wonderful.